Apex cardiography in silent myocardial ischemia diagnostics - N. A. Kozinsky; V. A. Lusov; V. G. Stranin (Российский кардиологический журнал)
The study involved 134 patients with coronary heart disease (CHD), aged 28-63, including 115 individuals with stable angina (functional class II), and 19 - with myocardial infarction in anamnesis. All patients underwent apex cardiography (ACG) with nitroglycerin during pain episode-free period. In patients with coronary occlusion, nitroglycerin-induced ACG dynamics was manifested only in поп-significantly diminished systolic wave asynergia, and decreased atrial complex amplitude. Patients without coronary occlusion demonstrated complete normalization of ACG. In all cases, with nitroglycerine effect reducing and, at last, disappearing, ACG returned to its baseline shape, registered before nitroglycerine administration. ACG curve typical for consistent, chronic silent coronarospasm was registered, being a manifestation of silent myocardial ischemia.